2016
DOI: 10.1371/journal.pone.0165649
|View full text |Cite|
|
Sign up to set email alerts
|

Development of the Nervous System of Carinina ochracea (Palaeonemer-tea, Nemertea)

Abstract: The various clades of Lophotrochozoa possess highly disparate adult morphologies. Most of them, including Nemertea (ribbon worms), are postulated to develop via a pelagic larva of the trochophora type, which is regarded as plesiomorphic in Lophotrochozoa. With respect to the nervous system, the trochophora larva displays a set of stereotypic features, including an apical organ and trochal neurites, both of which are lost at the onset of metamorphosis. In the investigated larvae of Nemertea, the nervous system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…A comparable situation is encountered in the development of the nervous system components with immuno-fluorescent methods, with the serotonin-immunoreactive (5HT-lir) component having been subject to more detailed analyses. Data on the development of the 5HT-lir nervous system is available for the pilidiophoran species M. alaskensis, Lineus albocinctus, as well as an unidentified pilidium-larva of the gyrans-type (supposedly Micrura purpurea) (Hay-Schmidt, 1990;Maslakova, 2010b;Hindinger et al, 2013); for the hoplonemertean species Quasitetrastemma stimpsoni and P. californiensis (Chernyshev and Magarlamov, 2010;Hiebert and Maslakova, 2015a); and for the palaeonemertean species Carinina ochracea (von Döhren, 2016). Data on the development of the RFa-lir component of the nervous system are scarcer, having only been published for the palaeonemertean species C. ochracea and the pilidium larvae of two heteronemertean Pilidiophora, L. albocinctus and an unidentified pilidium-larva of the gyrans-type, tentatively assigned to M. purpurea (Hay-Schmidt, 1990;Hindinger et al, 2013;von Döhren, 2016).…”
Section: Novel Findings On the Development Of Body-wall Muscles And Rfa-lir Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparable situation is encountered in the development of the nervous system components with immuno-fluorescent methods, with the serotonin-immunoreactive (5HT-lir) component having been subject to more detailed analyses. Data on the development of the 5HT-lir nervous system is available for the pilidiophoran species M. alaskensis, Lineus albocinctus, as well as an unidentified pilidium-larva of the gyrans-type (supposedly Micrura purpurea) (Hay-Schmidt, 1990;Maslakova, 2010b;Hindinger et al, 2013); for the hoplonemertean species Quasitetrastemma stimpsoni and P. californiensis (Chernyshev and Magarlamov, 2010;Hiebert and Maslakova, 2015a); and for the palaeonemertean species Carinina ochracea (von Döhren, 2016). Data on the development of the RFa-lir component of the nervous system are scarcer, having only been published for the palaeonemertean species C. ochracea and the pilidium larvae of two heteronemertean Pilidiophora, L. albocinctus and an unidentified pilidium-larva of the gyrans-type, tentatively assigned to M. purpurea (Hay-Schmidt, 1990;Hindinger et al, 2013;von Döhren, 2016).…”
Section: Novel Findings On the Development Of Body-wall Muscles And Rfa-lir Nervous Systemmentioning
confidence: 99%
“…With respect to development of nervous system and musculature, nemertean larvae are clearly understudied. Information on the development of the nervous system of Nemertea by means of fluorescent antibody labeling and confocal microscopy is almost exclusively restricted to the serotonin immunoreactive component in about a handful of mostly pilidiophoran species and the development of the body wall musculature by fluorescent labeling with phalloidin has never been in the focus of any comparative investigation (Hay-Schmidt, 1990;Martindale and Henry, 1995;Maslakova et al, 2004;Schwartz, 2009;Chernyshev and Magarlamov, 2010;Hiebert et al, 2010;Maslakova, 2010b;von Döhren, 2011von Döhren, , 2015von Döhren, , 2016Chernyshev et al, 2013;Hindinger et al, 2013;Hiebert and Maslakova, 2015a,b;Martín-Durán et al, 2015). This study aims at a comparative description of the development of the body wall musculature and of the FMRFamide immunoreactive component, a subset of the peptidergic nervous system in several non-pilidiophoran representatives that possess the type of development that has traditionally been termed as "direct."…”
Section: Introductionmentioning
confidence: 99%
“…The apical and subapical neurons are connected by two additional apical neurons, and we propose that these six neurons, i.e., two apical neurons, two subapical neurons, and two additional neurons, form an interconnected complex, which appears to be a component of the larval apical organ. The fate of the apical organ neurons in hoplonemertean species is not clear; some authors suggested that these neurons are completely resorbed during metamorphosis [50,56], whereas other reports indicated that some apical neurons persist through the metamorphosis as components of the brain ring [13,14,58]. This study on swimming larvae in the vermicular stage (7 dpf) revealed six apical neurons but their connections to the brain ring and the apical plate cells were fully resorbed.…”
Section: Apical Organs Of the Palaeo-and Hoplonemertean Larvaementioning
confidence: 73%
“…The analysis of the apical organ structure of palaeonemertean larvae, which is mainly limited to light-optical data, revealed a well-developed apical plate with an apical tuft. A study of the larvae (1 dpf) of the palaeonemertean Carinina ochracea identified two types of 5-HT-lir flask-shaped cells, one in the apical and median position and another in the medio-ventral position [56]. Available data do not allow a comparison of the apical organ of the paleonemertean larvae with those of the Pilidiophora and Hoplonemertea larvae.…”
Section: Apical Organs Of the Palaeo-and Hoplonemertean Larvaementioning
confidence: 98%
“…The major postpharyngeal commissure, which ventrally connects the lateral nerve cords, is the only juvenile neural structure which does not correspond directly to any of the elements of the adult nervous system of L. ruber [20, 22, 29] or, to our best knowledge, of any other nemertean, which nervous system has been studied thus far [e.g. 17-19, 20, 21, 28, 55-58]. In adult nemerteans, the lateral nerve cords are connected by numerous delicate ventral commissures, that are composed just of bundles of neurites and are considered as part of the peripheral nervous system.…”
Section: Discussionmentioning
confidence: 99%